Risk and uncertainty reduction by using algebraic inequalities - Todinov, M. T. (Boca Raton, FL : CRC Press, 2020)
"This book provides the reader with a domain-independent method for reducing risk through maximizing reliability, reducing epistemic uncertainty, reducing aleatory uncertainty, ranking the reliabilities of systems and processes, minimizing the risk of faulty assemblies, and ranking decision-making alternatives in the presence of deep uncertainty"--
OCLC-licensed vendor bibliographic record.
Keywords: Risk assessment -- Mathematics; System failures -- Prevention -- Mathematics; Risk management -- Mathematics; Inequalities (Mathematics); TECHNOLOGY / Manufacturing; MATHEMATICS / Mathematical Analysis; MATHEMATICS / Probability & Statistics / General